An investigation into the failure mechanism of severe abrasion of high-speed train brake discs on snowy days. (July 2019) - Wu, Ying; Liu, Yan; Chen, Hui; Chen, Yong; Xie, Di
Abstract: The brake discs of high-speed trains undergo severe abrasion on snowy days, which damages the safety of railway transportation. In the present paper, the mechanism leadinig to severe abrasion failure of brake discs in snowy days was determined. The microstructure and morphology of the scrap, damaged brake discs and pads were examined. The chemical composition of scrap surfaces was investigated. The ice wrapping the pads was collected and the inclusion in the ice was inspected. Moreover, camera surveillance was used to record the braking process on snowy days. Based on the results, a model for illustrating the severe abrasion process of brake discs was established. The hard particles in the ice wrapping brake pads scratched the brake disc and generated some swarf in the beginning. The swarf stacked and worked as abrasive material to gouge the brake discs, causing the severe abrasion failure finally. To demonstrate the model, reduced scale dynamo tests were carried out to simulate the severe abrasion according to speculation of the model, and similar results consistent with the actual situation were obtained. Highlights: The failure mechanism of severe abrasion of the brake discs in snowy days was revealed; A model for illustrating the mechanism of severe abrasion process of brake disc was established; The reduced scale dynamo tests were carried out to verify the model's validity.